Orbital Burkitt’s Lymphoma: An Aggressive Presentation - Gian Paolo Giuliari; Ama Sadaka; Maria Angelica Cortez; Antonina Paniagua (Case Reports in Ophthalmological Medicine)
Objective. To present the case of an aggressive orbital Burkitt’s lymphoma. Methods. Chart review. Case Presentation. A 24-year-old Haitian man came to our clinic complaining of rapidly progressive right eye proptosis. On examination, a large friable exophytic mass with necrotic areas and exudative/hemorrhagic secretions was noted protruding from his right orbit. A biopsy revealed the characteristic “starry-sky” appearance of a Burkitt lymphoma. The patient died shortly after due to complications from systemic involvement. Discussion. This case is meant to raise physicians’ awareness on the healthcare situation in some underdeveloped countries, emphasizing the importance of education in preventive medicine.